Monitoring and Assessment of Sal forest Infected by the Insect - Hoplocerambyx spinicornis, Using Remote Sensing and GIS - Pant, Daya N.; Roy, Parth S.; Phounsavath, Bouakeo (Indian Forester, 2002)
Sal forests play a dominant role in terms of their economic and ecological values. However, in many parts of India, these forests have been subjected to heavy damage by the serious pest Hoplocerambyx spinicornis. Remote sensing techniques supplemented with Global Positioning System (GPS) based ground truth information are capable for the identification and assessment of such damages. The study has been aimed at the preparation of the digital map of Sal forest infected by the pest and evolving the management st"rategy for its prevention and control. The Indian Remote Sensing Satellite data of 1999, 1998 and 1990 were analysed digitally in conjunction with GPS based ground sample information. The GIS data base for forest management units and other important physical feature were generated. Both the remote sensing and GIS data base were integrated and analysed. The study revealed the actual extent of damage as 23.4%, 21.6% and 6.2% during the period 1999, 1998 and 1990 respectively. The intensity of pest damage consisting of the categories >75%, 50-75%, 30-<50% and 10-<30% trees infected by Hoplocerambyx spinicornis has also been identified and analysed.